Effectiveness of Balloon Blowing Exercise on Oxygen Saturation in COPD Patients: A Pre-Experimental Study - Lutfi Wahyuni; Rizma Dwi Ramadina; Hevi Febriari Atika Utami (Universitas Airlangga, 2026)
Introduction: develop hypoxemia and hypercapnia as a result of weakening respiratory muscles. This reduces the oxygen saturation in the bodies of COPD patients. Balloon blowing exercise can improve oxygen transport, aid patients prolong exhalation, and promote healthy lung development, hence increasing oxygen saturation. The goal of this study was to assess the impact of balloon blowing exercise on oxygen saturation in COPD patients. Method: The research method used was pre-experimental with one group pre-post test design. Respondents used were 127 COPD patients through consecutive sampling technique. The instruments used were pulse oximetry and observation sheet. The intervention was carried out routinely 10 minutes per day for 4 weeks. Results: Of the 127 COPD patients, only 2 people did not experience an increase in oxygen saturation after the intervention. The results of the Wilcoxon statistical test obtained a p-value of 0.000. Conclusions: The results showed that balloon blowing exercise is effective in increasing oxygen saturation in COPD patients.